Actualization of the Force Majeure Clausula in the Law of Agreement in the Middle of Pandemic COVID-19 - Nur Azmi, Rama Halim; Hilmy, Muhammad Irfan (Lex Scientia Law Review, 2020)
As the governing body for social life, the existence of law cannot just be released. The importance of law in human life is solely for creating justice and order. One of the essences of the law itself is that there are rules for the relationship between the state and its people and between individuals. In general, laws that regulate relationships between individuals in society are civil laws. In civil law, there are several scopes including agreement. An agreement is essentially an agreement between the parties which then creates a legal relationship between the parties. However, in its application, there are several reasons that can be used by either party for not fulfilling its achievement. One of the reasons for this is force majeure or better known as a state of force. In general, the state of force is only synonymous with natural disasters or the act of God. But now the scope of force majeure has expanded in practice. Currently, almost all countries in the world are being hit by the COVID-19 pandemic. This pandemic condition certainly affects all aspects of life, including the enforcement of an agreement. Through this paper the author will discuss the conception of force majeure and how it correlates with the current pandemic situation. The method used in this paper is normative juridical approach to laws and regulations, conceptual approaches, and case approaches.